2014
DOI: 10.3389/fphys.2014.00280
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic dysfunction in vasovagal syncope and the postural orthostatic tachycardia syndrome

Abstract: Orthostatic intolerance is the inability to tolerate the upright posture and is relieved by recumbence. It most commonly affects young women and has a major impact on quality of life and psychosocial well-being. Several forms of orthostatic intolerance have been described. The most common one is the recurrent vasovagal syncope (VVS) phenotype which presents as a transient and abrupt loss of consciousness and postural tone that is followed by rapid recovery. Another common type of orthostatic intolerance is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 75 publications
1
51
0
1
Order By: Relevance
“…(23,24). Both reflex syncope and postural orthostatic tachycardia syndrome have been discussed in detail elsewhere (22,(25)(26)(27).…”
Section: The Homeostatic Regulation Of Blood Pressurementioning
confidence: 99%
“…(23,24). Both reflex syncope and postural orthostatic tachycardia syndrome have been discussed in detail elsewhere (22,(25)(26)(27).…”
Section: The Homeostatic Regulation Of Blood Pressurementioning
confidence: 99%
“…OH is defined as a decrease in systolic blood pressure or diastolic pressure on standing compared to a sitting or supine position. The POTS is characterized by an excessive increase in the heart rate upon standing and is associated with symptoms of OI [2]. OI may cause injury, and epidemiological studies have confirmed that OI is an independent risk factor for coronary heart disease, stroke, and renal failure [1].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, an impairment of the compensatory response to upright posture can lead to decreased cerebral perfusion and an inability to tolerate the upright posture, termed orthostatic intolerance (OI) [1]. The symptoms of OI are fatigue, blurred vision, dizziness, nausea, abdominal pain, and syncope [2]. The main types of OI consist of orthostatic hypotension (OH) and postural orthostatic tachycardia syndrome (POTS) according to response to head-up tilt table test (HUT) [3].…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Clinical management is complex, largely due to lack of knowledge about pathophysiological mechanisms. Previous studies have shown that neurohumoral changes, 4 deconditioning, 5 and hypovolemia 6 may be involved.…”
Section: Introductionmentioning
confidence: 99%